Makna Wudhu dalam Kehidupan menurut Al-Qur'an dan Hadis - Kusumawardani, Diah (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this study is to discuss the meaning of ablution in life according to the Qur'an and the hadith of the Prophet. This research method uses a qualitative type through literature study with content analysis. The results and discussion of this study include general views on ablution, the arguments of the Qur'an and hadith about ablution, and the influence of ablution in life. This study concludes that by performing ablution according to the guidance taught by the Prophet Muhammad and living every washing and ablution movements as well as the motivation from within to maintain ablution so as to make all subjects able to overcome obstacles and challenges. This research is expected to have benefits for enriching the treasures of Islamic knowledge.